How to Enhance the Effects of Mediated Intergroup Contact? Evidence from Four Countries. Issue 1 (2nd January 2020) - Wojcieszak, Magdalena; Kim, Nuri; Igartua, Juan-José
Abstract : We bridge the theorizing on mediated and imagined contact and integrate these two contact forms in one sequence within a single design. We experimentally examine whether (1) encouraging people to imagine a positive intergroup encounter prior to reading a personal story of an outgroup member as well as (2) mediated contact with an outgroup member similar or dissimilar to the ingroup prototype, improve outgroup attitudes. We also test the affective and cognitive mediators through which these effects emerge. Data from four different countries that test attitudes toward four distinct immigrant groups find that although imagined contact and similarity do not consistently improve outgroup attitudes, enhanced interest in the story of an outgroup member and positive emotions mediate the effects from similarity, and – in two countries – from imagined contact. Theoretical and practical implications of the findings are discussed.